To update or not to update: Insights From a two-year study of Android app evolution - Taylor, V; Martinovic, I (Association for Computing Machinery, 2017)
Although there are over 1,900,000 third-party Android apps in the Google Play Store, little is understood about how their security and privacy characteristics, such as dangerous permission usage and the vulnerabilities they contain, have evolved over time. Our research is two-fold: we take quarterly snapshots of the Google Play Store over a two-year period to understand how permission usage by apps has changed; and we analyse 30,000 apps to understand how their security and privacy characteristics have changed over the same two-year period. Extrapolating our findings, we estimate that over 35,000 apps in the Google Play Store ask for additional dangerous permissions every three months. Our statistically significant observations suggest that free apps and popular apps are more likely to ask for additional dangerous permissions when they are updated. Worryingly, we discover that Android apps are not getting safer as they are updated. In many cases, app updates serve to increase the number of distinct vulnerabilities contained within apps, especially for popular apps. We conclude with recommendations to stakeholders for improving the security of the Android ecosystem.